THE SOLUTION TO A SYSTEM OF EQUATIONS OF THE HOPFTYPE IN THE FORM OF A TRAVELING WAVE - Turdiev, U.Q.; Axmedova, M.; Juraqobilov, A. (SCIENCE and SOCIETY, 2026)
From the system of non-stationary equations of two-velocity hydrodynamics, a system of equations of the Burgers and Hopf type was obtained. It should be taken into account that energy dissipation occurs due to the viscosity of the subsystems and the coefficient of friction between the components. Analysis of the system of differential equations in the form of traveling waves for the Hopf-type model reduces the system to solving a system of nonlinear ordinary differential equations.